The effects of feed withdrawal, transport and lairage on intestinal microflora in broiler chickens - Zainool Abidin, Zulaikha; Hafiy Idris, Fahim; Kumari Ramiah, Suriya; Atta Awad, Elmutaz; Zakaria, Zunita; Idrus, Zulkifli (ResearchersLinks, 2022)
This study investigated the effects of stressful pre-slaughter practices, namely feed withdrawal, road transportation, and lairage, on the caecal population Salmonella spp., Campylobacter spp., E. coli, Clostridium spp., and Lactobacillus spp. in broiler chickens. Thirty-five-day-old broiler chickens were subjected to either 0 h or 8 h of feed withdrawal, followed by 2 h or 4 h of road transportation. For each feed withdrawal-transportation subgroup, the birds were lairaged for 0 h or 3 h. Salmonella spp. and Campylobacter spp. were only detected in two and three birds, respectively. Because of the insufficient data, both types of bacteria were excluded from the study. Eight hours of feed withdrawal increased the population of Lactobacilli significantly but had a negligible effect on E. coli and Clostridium spp. counts. Prolonged duration of road transportation and lairage increased caecal counts of E coli. Birds road transported for 8 h had a higher caecal population of Clostridium spp. but lairage duration had no significance on the bacteria. In conclusion, the present findings strengthen the notion that minimising the stress associated with pre-slaughter practices is important to maintain the safety of broiler chicken meat.